Media Discourse on Sustainable Consumption in Europe. Issue 3 (3rd April 2022) - Diaconeasa, Maria-Claudia; Popescu, Gabriel; Maehle, Natalia; Nelgen, Signe; Capitello, Roberta
ABSTRACT: Given the importance of mass media in forming consumer attitudes, exploring the main trends in the media discourse on sustainability is of great interest to businesses, policymakers and researchers. This study investigates the discourse on sustainable consumption in major national newspapers in four European countries (Germany, Italy, Norway and Romania), using food consumption as the specific topic. It provides a comprehensive analysis of the issues reported in the newspapers related to the concept of sustainable food from the longitudinal and comparative perspective and identifies the dimensions of sustainability reported in the examined newspapers that are associated with sustainable food in the four different countries. This study adds to the understanding of how the sustainable food concept has developed in Europe over time and highlights the factors that have influenced the development of this concept. The information gaps in the common understanding of the sustainable food concept are pointed out through this research, therefore illustrating how to enhance consumer awareness about this issue.